Financial crises in emerging markets: a canonical model - Roberto Chang; Andres Velasco (Federal Reserve Bank of Atlanta, 1998)
We present a simple model that can account for the main features of recent financial crises in emerging markets. The international illiquidity of the domestic financial system is at the center of the problem. Illiquid banks are a necessary and a sufficient condition for financial crises to occur. Domestic financial liberalization and capital flows from abroad (especially if short-term) can aggravate the illiquidity of banks and increase their vulnerability to exogenous shocks and shifts in expectations. A bank collapse multiplies the harmful effects of an initial shock, as a credit squeeze and costly liquidation of investment projects cause real output drops and collapses in asset prices. Under fixed exchange rates, a run on banks becomes a run on the currency if the central bank attempts to act as a lender of last resort.
Keywords: 330; Banks and banking; Central; International finance; Liquidity (Economics); Monetary policy; Money supply